Potensi Thorium dan Uranium di Kabupaten Bangka Barat - Ngadenin, Ngadenin; Syaeful, Heri; Widana, Kurnia Setiawan; Nurdin, Muhammad (EKSPLORIUM, 2014)
Thorium and uranium in Bangka Island are mainly found in monazite mineral. In the geological point of view the monazite formed in S type granite, sandstones and alluvial deposits. In Bangka Baratwhere several S types granite and also alluvial deposites and this area considered as a potential area for monazite placer. S type granites are predicted as a source of monazite while alluvial deposits are considered as a dispersion place for deposition of monazite. The purpose of this study is to determine the geological information and to know the hypothetical potency of thorium and uranium resources in alluvial deposits. The methodsusedin this study are geological mapping, measurement of thorium and uranium contents in the rock, sampling of granite for petrographic analysis, sampling of heavy mineral in alluvial deposits for grain size analysis. Results of the research show that the lithology of West Bangka region composed of schist unit, meta-sandstone unit, granite intrusion, diabase intrusion, sandstone unit and alluvial deposits. Monazite is found in granite intrusion, sandstone unit and alluvial deposits. Evolving fault strend to northwest-southeast, northeast-southwest and west-east.The results of the grain size analysis of heavy mineral shows the average percentage of monazite in the heavy mineral is 6.34%. Other potential minerals contained in placer deposits are zircon 36.65%, ilmenite 19.67% and cassiterite 14.75%.